Management practices in parish-based schools - Sigua, Edgardo S. 1965- (2008)
This study focused on the assessment of management practices of priest-administrators in the Ecclesiastical Province (Catholic Church) in Region 3 for the School Year 2006-07. The design utilized the descriptive method. The respondents are priests and school administrators who belong to parochial schools in dioceses which comprises the ecclesiastical province in Region 3. Findings revealed that administrators of parish-based schools are usually priests assigned as superintendents, directors, assistant directors, principals, administrative staff. They strongly agree that in their management practices, informational, interpersonal, and decisional roles are performed. It can be concluded that the typical school administrators of parish-based schools are priests belonging to the middle adulthood (46 years old) and mostly have finished master's degree and have stayed in their position for quite a number of years.